Development of a Norovirus P Particle Platform for Eliciting Neutralizing Antibody Responses to the Membrane Proximal External Region of Human Immunodeficiency Virus Type 1 Envelope - Zang, Yang; Bi, Jinpeng; Du, Dongchuan; Liu, Xintao; Zhang, Yan; Su, Weiheng; Wu, Jiaxin; Shan, Yaming; Wang, Song; Kong, Wei; Qiu, Aidong; Jiang, Chunlai (Protein and Peptide Letters, 2014)
Eliciting efficient broadly neutralizing antibodies (BnAbs) is an important goal that has yet to be achieved for human immunodeficiency type 1 (HIV-1) vaccine development, although they are rarely produced in virus-infected individuals. In particular, inducing specific neutralizing antibodies to the gp41 membrane proximal external region (MPER) has proven a difficult task. In this study, we introduce Norovirus P particles as a new platform to display the MPER epitope of HIV-1 as a vaccine with the aim of enhancing immune responses. The results showed that HIV-1 chimeric P particles were capable of inducing MPER-specific antibody responses in immunized guinea pigs, although only weakly neutralizing activity could be detected. These findings are consistent with other previous studies which have also focused on the well-studied 2F5 and 4E10 BnAbs. Our findings provide an alternate strategy for design of vaccines against HIV-1. However, great challenges remain in the effort to develop vaccines that can induce efficient HIV-1 neutralizing antibodies.
Keywords: MPER